2021
DOI: 10.1111/scs.13036
|View full text |Cite
|
Sign up to set email alerts
|

Katie Eriksson’s caring theories. Part 1. The caritative caring theory, the multidimensional health theory and the theory of human suffering

Abstract: In this article, Katie Eriksson's caring theories including the caritative caring theory, the multidimensional health theory and the theory of human suffering are described. The assumptions and concepts, both etymologically and semantically investigated, are founded in ontology. Caring is a human natural phenomenon and patient means the suffering human being. In the caritative caring theory, the substance and core of caring is described as ‘to care is to tend, play and learn in faith, hope and love’. The start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 9 publications
1
50
0
Order By: Relevance
“…Having a personal touch was provided when healthcare professionals emphasized, accepted, and understood patient needs with compassion, love, and mercy. Several people in our study indicated that caring seemed to come naturally for them, and that care can be understood as a natural phenomenon for the human being (Bergbom et al 2021). This suggests that people who have a natural ability to show compassion, love, and mercy, are more able and better prepared to provide and care for patient spiritual needs and provide good care (Eriksson 1997).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Having a personal touch was provided when healthcare professionals emphasized, accepted, and understood patient needs with compassion, love, and mercy. Several people in our study indicated that caring seemed to come naturally for them, and that care can be understood as a natural phenomenon for the human being (Bergbom et al 2021). This suggests that people who have a natural ability to show compassion, love, and mercy, are more able and better prepared to provide and care for patient spiritual needs and provide good care (Eriksson 1997).…”
Section: Discussionmentioning
confidence: 72%
“…Participants understood spirituality as an integrated dimension of whole-person care and related it to how one copes with changes in health and suffering (Bergbom et al 2021;Eriksson 2002). At the same time, several people did not acknowledge the spiritual dimension, and after hearing the definition from EAPC (2021), they understood spiritual care as being equal to good care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Caring leadership comes naturally from characteristics, evidenced by a supportive leader-follower relationship, which is critical to achieving the Institute of Healthcare's vision of nurses as full partners with other health care professionals (Peng et al, 2015). Eriksson's Caritative theory illustrated caring through relationships that involve love, mercy and compassion; the motive of caring is to alleviate suffering and protect well-being (Bergbom et al, 2021). In Eriksson's theory, caring is a natural process deeply connected with human suffering and helps to understand the essence of caring.…”
mentioning
confidence: 99%